(untitled) (Colombia Medica, 2008)
Introduction: Malaria infection, anaemia and intestinal parasitism, are important public health problems in Colombia. Available data suggests that these are not separate conditions, but interrelated. On the other hand, retinol supplementation successfully decreases mortality in children. In malaria endemic areas, this supplement reduces severe malaria in children, due to immune modulation by retinol. For example, retinoic acid induced a bias towards a TH2 immune response, an event that is associated with protection against severe anaemia. This review aimed at describing some relationships, reported in global biomedical literature, between retinol and malaria; retinol and anaemia; retinol, malaria and intestinal parasites; anaemia and malaria; and to how the TH1/TH2 cytokine pattern in individuals with malaria changes according to retinol supplementation. Methods: The following biomedical literature databases were consulted: Medline, Lilacs, Spingerlik, Md. Consultant, Web of Science, Ovid, Scient Direct, Ebsco and Cochrane. Information documenting prevalence of malnutrition, subclinical retinol deficiency, anaemia and malaria in Colombian children, as well as papers on the anti-infectious role of retinol were also. Results: A relationship between malaria and intestinal parasitic infections was reported. Some studies indicate that helminth infection predispose children to suffer malaria. On the other hand, these intestinal parasites have also been associated with anaemia and low retinol plasma concentrations, which in turn are associated with malaria. No co-relation regarding a simultaneous link between all these conditions, and the TH1/TH2 balance was observed. Conclusions: The study of associations between malaria, anaemia, intestinal parasite infections and low retinol level, with the TH1/TH2 cytokine response as centerpiece is essential to prevent or provide early treatment.